Strategi Pengembangan Objek Wisata dalam Upaya Meningkatkan Kunjungan Wisatawan : Studi Pada Objek Wisata Fulan Fehan - Wiligis Wilfrida Klau; Apriana H. J. Fanggidae; Debryana Y. Salean; Ronald P. C. Fanggidae (Jurnal Studi Perhotelan dan Pariwisata, 2023)
Purpose: The aim of this research is to describe a tourism development strategy in increasing visits to the Fulan Fehan tourist attraction. Methodology: The type of research used is descriptive qualitative research, where the researcher intends to describe existing phenomena by analyzing and presenting existing facts systematically to facilitate understanding and drawing conclusions. By using the Qualitative Method, the data obtained will be more complete, more in-depth, credible, and meaningful, so that the research objectives can be achieved. The population in this study includes people who are considered and are seen to know correctly about the Fulan Fehan tourist attraction. In this study the method used to analyze the development strategy of Fulan Fehan's tourist attraction in Belu Regency is by using SWOT analysis. Result: Things that can be done to increase tourist visits to the Fulan Fehan tourist attraction are to add supporting facilities and infrastructure such as lodging, lopo-lopo, food stalls, parking lots, trash cans and other supporting facilities, as well as maintaining the facilities and infrastructure that is already available so that damage does not occur so that it is attractive and provides comfort for visitors.